(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Islamic Religious Education (PAI) as one of the subjects in schools needs to follow this development by adapting a curriculum that is in accordance with the demands of the times. This research aims to explore how to develop a PAI curriculum that is adaptive to the development of digital technology. This research uses a qualitative approach with a literature study method that utilizes previous writings such as books, journals, and articles. Content analysis and descriptive analysis are the basis for this research. Propositions and concepts are supported by a comprehensive and critical literature analysis from a variety of sources. The results of the analysis show that the development of an Islamic Religious Education curriculum that is adaptive to the development of digital technology involves the use of digital technology in learning such as interactive multimedia, e-learning platforms, mobile applications, virtual reality, and augmented reality to increase students’ interest, motivation, and learning experience. This curriculum also includes the development of quality digital teaching materials such as interactive e-books, learning videos, and the use of e-learning platforms. In addition, training is needed for PAI teachers in integrating digital technology into learning, including the use of digital devices, the development of digital teaching materials, the use of e-learning platforms, digital learning strategies, and the ethics and safety of technology use